2004
DOI: 10.2337/diabetes.53.3.847
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Peroxisome Proliferator-Activated Receptor δ Associated With Obesity

Abstract: Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors regulating the expression of genes involved in lipid and glucose metabolism. Three different PPARs, PPAR-␣, -␥, and -␦, have been characterized, and they are distinguished from each other by tissue distribution and cell activation. All PPARs are, to different extents, activated by fatty acids and derivatives. Recently, it has been shown that PPAR-␦ serves as a widespread regulator of fat burning, suggesting that it might be a potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 18 publications
6
71
1
Order By: Relevance
“…The frequency of the À87C allele was of 20.1% and was similar to the frequency observed in a sample of Korean subjects 15 and in a Scotland population with coronary heart disease (CHD) 16 but was slightly higher than that in healthy subjects from Sweden (15.6%). 14 Although these results must Abbreviations: BMI, body mass index; HDL, high-density lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; PPAR, peroxisome proliferator-activated receptor.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The frequency of the À87C allele was of 20.1% and was similar to the frequency observed in a sample of Korean subjects 15 and in a Scotland population with coronary heart disease (CHD) 16 but was slightly higher than that in healthy subjects from Sweden (15.6%). 14 Although these results must Abbreviations: BMI, body mass index; HDL, high-density lipoprotein cholesterol; LDL-C, low-density lipoprotein cholesterol; PPAR, peroxisome proliferator-activated receptor.…”
Section: Discussionsupporting
confidence: 80%
“…Two previous studies performed by Skogsberg et al 14,16 have been performed with male subjects and found no association in one study and lower plasma HDL-C levels in À87C carriers in the other study. Another study performed by Shin et al 15 showed no association with plasma HDL-C levels. Unfortunately, these data were not analyzed separately by sex.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The minor allele of the rs2016520 variant in exon 4 has inconsistently been associated with decreased fasting levels of HDL-cholesterol [15], increased LDL-cholesterol a Regression estimate±SE of the logarithm of HOMA-IR (pmol/l×mmol/l) with haplotype 1 (A-C) as base Haplotype frequencies were estimated using the EM algorithm and association with quantitative traits was evaluated by global and haplotypespecific score statistics ( p value) and simulation (p SIM ) [31] Estimates of the effect sizes of each haplotype were estimated by modelling the haplotype×phenotype interaction [32] [16,17] and increased fasting plasma glucose [37] or decreased BMI [20], even though some studies found no association [19,21]. Yet all studies were probably statistically underpowered, involving fewer than 1,000 participants.…”
Section: Discussionmentioning
confidence: 99%